Identification and functional characteristics of a novel splicing heterozygote variant of COL2A1 associated with Stickler syndrome type I - Gong, Yujing; Zhu, Weijian; Zhu, Mianmian; Chen, Dan; Wu, Sunke; Hu, Sisi; Luo, Yi; Jiang, Yiyi; Zhu, Ting; Wang, Dan (Frontiers in Genetics, 2024)
Background Stickler syndrome type I (STL1) is an autosomal dominant disorder characterized by ocular, auditory, orofacial, and skeletal anomalies. The main causes of STL1 are variants in the COL2A1 gene, which encodes a type II collagen precursor protein. The specific focus of this study was on a newborn from China diagnosed with STL1, with the aim of providing novel insights into the effects of a newly identified intronic variant in the COL2A1 gene on pre-mRNA splicing.Methods Trio whole exome sequencing was used to identify the causative variant in the family. The identified variant was validated using Sanger sequencing. Bioinformatics programs were used to predict the pathogenicity of the candidate variant. Additionally, an in vitro minigene assay was used to investigate the effects of the identified variant on RNA splicing.The proband with STL1 had a novel heterozygous splicing variant in the intron 9 acceptor donor site of COL2A1 (c.655-2A>G). This splice junction variant resulted in aberrant COL2A1 mRNA splicing, leading to the skipping of exon 10 and the production of a shorter protein that may lack the last 18 native amino acids.The c.655-2A>G variant in the COL2A1 gene leads to STL1 through abnormal splicing.By expanding the spectrum of variants in the COL2A1 gene, this finding improves the clinical understanding of STL1 and provides guidance for early diagnosis and disease counseling.